A Control Scheme That Uses Dynamic Postural Synergies to Coordinate a Hybrid Walking Neuroprosthesis: Theory and Experiments - Alibeji, Naji A.; Molazadeh, Vahidreza; Dicianno, Brad E.; Sharma, Nitin (Frontiers in Neuroscience, 2018)
Abstract--- A hybrid walking neuroprosthesis that combines functional electrical stimulation (FES) with a powered lower limb exoskeleton provides therapeutic benefits of FES and torque reliability of the powered exoskeleton. Moreover, by harnessing metabolic power of muscles via FES the hybrid combination has a potential of lowering power consumption and reducing actuator size for the powered exoskeleton. Its control design, however, must overcome the challenges of actuator redundancy due to the combined use of FES and electric motor. Further, to maintain stability and control performance when disparate dynamics of FES and electric motor are combined, dynamical disturbances such as electromechanical delay (EMD) and muscle fatigue must be considered during the control design process. In this paper, a general framework to coordinate FES of multiple gait-governing muscles with electric motors is presented. A human motor control-inspired synergy-based control framework is used to derive the controller and is motivated mainly to address the actuator redundancy issue. Dynamic postural synergies between FES of the muscles and the electric motors were artificially generated through optimizations and result in key dynamic postures when activated. These synergies were used in the feedforward path of the control system. A dynamic surface control technique, modified with a delay compensation term, is used as the feedback controller to address model uncertainty, the cascaded muscle activation dynamics, and EMD. To address muscle fatigue, the stimulation levels in the feedforward path were gradually increased based on a model-based fatigue estimate. A Lyapunov-based stability approach was used to derive the controllers and guarantee their stability. The synergy-based controller was demonstrated experimentally on an able-bodied subject and person with an incomplete SCI.